FAR-INFRARED SATURATION SPECTROSCOPY OF A SINGLE SQUARE-WELL - Craig, K.; Felix, C. L.; Heyman, J. N.; Markelz, A. G.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We have performed saturation spectroscopy measurements of the lowest intersubband transition in a single 400 angstrom GaAs/Al0.3Ga0.7As modulation-doped square quantum well. We couple intense tunable far-infrared radiation from the Santa Barbara free electron laser into our sample using an edge-coupling technique and measure absorption as a function of frequency and intensity. Saturation and frequency shifts in the absorption line are clearly observed. We attribute the frequency shifts to reductions in the many-body depolarization shift. From our preliminary measurements, we estimate the intersubband relaxation time to be 600 ps to within a factor of three.